Presentation dossier: Kant 300 PT – Grupo Kant Lisboa / Lisbon Kant Group - Lemos , João (Con-Textos Kantianos. International Journal of Philosophy, 2024)
The dossier ‘Kant 300 PT – Lisbon Kant Group / Grupo Kant Lisboa’ celebrates Immanuel Kant’s 300th birthday, focusing on the activities of the recently formed Lisbon Kant Group / Grupo Kant Lisboa. Among the authors contributing to the dossier are both members of the Group and colleagues who have been actively collaborating with the Group. The articles included in the dossier are all written in Portuguese and have as their central thematic line Kant’s practical philosophy, with a special emphasis on moral values and political philosophy, also referring to aesthetic values, anthropology, and philosophy of history. In celebrating Kant, this dossier also pays tribute to António Marques, the driving force behind the research being carried out by the Lisbon Kant Group / Grupo Kant Lisboa.
Keywords: Kant; practical philosophy; moral value; aesthetic value